Pengembangan Potensi Pangan Lokal sebagai Kuliner Khas di Desa Wae Bobok Kabupaten Manggarai Barat - Elisabet Oktaviani Hanggu; Gregorius Antariksa Berybe; Maria Beatriks Rahinart Wellalangi; Novita Masi Dari Tani; Rafael Modestus Ziku; Fransiskus Xaverius Daniel Lumenta (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2022)
Wae Bobok, Tanjung Boleng Village, Boleng District, West Manggarai Regency, East Nusa Tenggara (NTT) Province, has several ideal local food potentials to be developed into local specialties. This area has quite good agricultural potential in the form of rice, sweet potatoes, and various other food products. The strategic location of Wae Bobok village makes it a